Biomarkers in breast cancer - Laguens, Graciela (2006)
Breast cancer is one of the most frequently diagnosed cancers among women in the western world. Due to the aggressive behaviour of some specific types and the possibility of an early diagnosis, breast cancer has been constantly studied. Tumour size, histological type, cellular and nuclear characteristics, mitotic index, vascular invasion, hormonal receptors and axillary lymph node status are biomarkers routinely used. However, these parameters are not enough to predict the course of this disease. Molecular biology advances have made it possible to find new markers, which have already been incorporated to the clinical practice. Their ultimate goal is to reduce mortality by identifying women at risk for the development of this disease, help diagnosis, determine prognosis, detect recurrences, monitor and guide treatment, and in particular cancers they are suited for general screening. Tumour markers in breast cancer were ranked in categories reflecting their clinical utility, according to the American College of Pathologists. This article focuses on traditional and new molecular markers stratifying them into categories and emphasizing their relevance in the routine evaluation of patients with breast cancer.